2017
DOI: 10.1177/1043986217724537
|View full text |Cite
|
Sign up to set email alerts
|

The Issue of Racial Profiling in Traffic Stop Citations

Abstract: This study addresses racial profiling when the traffic stop outcome is a citation. This study uses focal concerns theory as a theoretical explanation for police officer decision-making while using propensity score matching to provide similarly situated drivers based on race and/or gender. This study uses traffic stop data (N = 48,586) collected by the Louisville Police Department between January 1 and December 31, 2002. The statistical results show that focal concerns theory components matter the most for traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The study by Vito et al (2017) found that traffic stops with Black drivers were less likely to generate citations compared to that of other races, but the researchers suggested that this could be explained because officers believed Blacks were involved in more serious crimes. According to Voigt et al (2017), police officer's utterances spoken to White community members during vehicle stops were consistently more respectful, but not more formal, than those directed at Black individuals, even after controlling for contextual factors such as the severity of the offense or the outcome of the stop.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Vito et al (2017) found that traffic stops with Black drivers were less likely to generate citations compared to that of other races, but the researchers suggested that this could be explained because officers believed Blacks were involved in more serious crimes. According to Voigt et al (2017), police officer's utterances spoken to White community members during vehicle stops were consistently more respectful, but not more formal, than those directed at Black individuals, even after controlling for contextual factors such as the severity of the offense or the outcome of the stop.…”
Section: Resultsmentioning
confidence: 99%
“…Prior research in the racial profiling literature regarding police decision making and traffic stops has shown the utility of applying focal concerns theory (Higgins et al 2012;Vito et al 2017Vito et al , 2018Vito et al , 2019. This study seeks to advance upon prior work on stop and frisk using focal concerns theory to explain officers' decision making and use propensity score matching for the statistical analysis.…”
Section: Focal Concerns Theorymentioning
confidence: 99%
“…A prevailing argument is that female suspects receive leniency by the criminal justice system due to chivalry and gender stereotypes of women as less dangerous (Steffensmeier, 1980 ; Visher, 1983 ). Due to these perceptions, officers may show female suspects leniency during incidents such as traffic stops (Tillyer & Engel, 2013 ); yet other evidence suggests gender does not affect police decision-making (Vito et al, 2017 ). These findings are in line with a focal concerns framework.…”
Section: Literature Reviewmentioning
confidence: 99%